EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1964)
Abstract The article presents some questions of theory accounts. The theory of accounts portion of the November 1963, Uniform Certified Public Accountants (CPA) examination was given on November 8, 1963. Suggested time allotments for questions are given in the article. Answers, which follow are intended to typify those submitted by well-prepared candidates writing within the time limits prescribed. They do not necessarily include all elements for which credit might be given by the Advisory Grading Service of the American Institute of CPA or by the various state accountancy boards charged with responsibility of issuing CPA certificates. In first section, all questions are compulsory. In the appropriate space on the separate answer sheet, candidates are required to blacken the space of the letter of the answer choice that best completes each statement. Candidates should use the special electrographic pencil for marking the answer sheet. Candidate has to mark only one answer for each numbered statement.